Experimental Study Of Wear Testing Of ASTM 440C Steel On A Ball-On-Disc Tribometer Using Variations Of Lubricants - Jhonatan Jufrianto Sitorus; Dicky Januarizky Silitonga; Putra Andi Kolala; Lathifa Putri Afisna; Devia Gahana Cindi Alfian (Jurnal Vokasi Mekanika (VoMek), 2025)
Bearings are important components in industry that function to reduce friction between moving parts for smoother and more efficient movement. However, friction that occurs can cause wear on the bearing surface. This study aims to analyze the wear volume, wear width, and wear rate of ASTM 440C steel material with variations of SAE 10W-30, SAE 10W-40, and SAE 140 lubricants at rotational speeds of 180 rpm, 270 rpm, and 310 rpm. Testing was carried out using a tribometer. ball-on-disc with a constant time of 10 minutes. The test results showed that the lowest wear width was obtained in SAE 10W-40 lubricant of 259.806 µm at 180 rpm, while the highest value of 417.894 µm also occurred in SAE 10W-40 at 270 rpm. The lowest wear volume was recorded in SAE 10W-40 of 0.0225 mm³ at 180 rpm, while the highest was 0.0942 mm³ at 270 rpm with the same lubricant. For the wear rate, the lowest value of 0.50 × 10?? g/mm²·s was found in SAE 140 lubricant at 180 rpm, while the highest was 1.58 × 10?? g/mm²·s occurred in SAE 10W-40 at 270 rpm. Overall, SAE 10W-40 lubricants are more suitable for use at low revs, while SAE 140 lubricants are recommended for high revs due to their greater viscosity and resistance to wear.